Perceived Organizational Support and Lecturer Professionalism: The Mediating Role of Job Satisfaction - Suriyanto, Suriyanto; Patisina; Lubis, Rahmi (Journal of Educational, Health and Community Psychology, 2025)
Lecturer professionalism is a crucial determinant of higher education quality, particularly in institutional contexts with limited structural support. This study examines the influence of Perceived Organizational Support (POS) on lecturer professionalism, with job satisfaction tested as a mediating variable. Employing a quantitative explanatory design, the study involved 293 certified lecturers under the coordination of KOPERTAIS Region IX, North Sumatra. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. The results revealed that POS had no direct and significant effect on lecturer professionalism (β = 0.130; p = 0.082), but significantly affected job satisfaction (β = 0.728; p = 0.000). Job satisfaction, in turn, exerted a significant positive effect on lecturer professionalism (β = 0.474; p = 0.000) and fully mediated the relationship between POS and professionalism (β = 0.345; p = 0.000). These findings suggest that perceptions of organizational support enhance lecturer professionalism only when translated into positive work experiences that foster psychological and affective job satisfaction. The study underscores the practical importance of adopting relational and humanistic approaches in academic human resource management to strengthen and sustain lecturer professionalism.